The Challenge of Saudi Vision 2030: Foreign Policy Dilemma of Saudi Arabia - Amal, Moh Talabul; Rahayu, Dini Septyana (Journal of Islamic World and Politics, 2024)
This research will discuss the impact of the US-China rivalry on the actualization of Saudi Vision 2030. The objective is to examine the impact of Saudi Arabia's strategic alliances with the United States and China on its ambitious reform plan. The research investigates the geopolitical and international relations dimensions of the roles played by the United States and China. The focus is on the United States as a strategic ally and economic partner and China as a significant collaborator for economic diversification. The study employed a descriptive methodology, focusing on secondary data from relevant literature on Saudi foreign policy and Saudi Vision 2030. The findings indicated that the contrasting impacts of the United States and China in Saudi Arabia pose significant challenges to the clarity and consistency of Saudi strategic decision-making. Saudi Arabia is confronted with a complex geopolitical dilemma, as strengthening its ties with one state may have a detrimental impact on its relations with the other and compromise the achievement of Vision 2030. The research argues that successfully navigating the complex international landscape requires the adoption of a well-balanced foreign policy plan. This approach should aim to optimize the benefits obtained from partnerships while also limiting the possible risks associated with them.